STRUCTURAL PLANNING OF 4 FLOOR BULDING OFFICE OF HIGH PROSECUTORS, CENTRAL JAVA - Saputra, Dicky Alga; Purwanto; Widorini, Trias; Crista, Ngudi Hari; Krisno, Gama Aji (Jurnal Civil Engineering Study, 2024)
Structural Planning of a building construction is needed to get the most effective and efficient dimensions and configuration of the structure. Planning of a building structure located in a prone area must be planned according to standards, strong, and earthquake safe. Structural Planning of a 4 - Story Building for the Central Java Attorney General's Office, referring to the Structural Concrete Requirements to refer to Buildings and Non-Buildings (Indonesian National Standard 03-1726-2019) and Minimum Loads for Designing Buildings and Other Structures (Indonesian National Standard 03-1727-2013). The planning of the 4-story building structure of the Central Java Prosecutor's Office includes the planning of the upper and lower structures. Planning the upper structure using SAP 2000 V14.2.2, while the lower structure is planned manually. The upper structure includes the planning of the roof, beams, columns, and floor plates of the building, while the lower structure includes the planning of the foundation. Loads that are reviewed for the design of structural elements are dead load, live load, and earthquake load. Earthquake load entered is dynamic earthquake load. Structural Planning of a building construction is needed to get the most effective and efficient dimensions and configuration of the structure. Planning of a building structure located in a prone area must be planned according to standards, strong, and earthquake safe. Structural Planning of a 4 - Story Building for the Central Java Attorney General's Office, referring to the Structural Concrete Requirements to refer to Buildings and Non-Buildings (Indonesian National Standard 03-1726-2019) and Minimum Loads for Designing Buildings and Other Structures (Indonesian National Standard 03-1727-2013). The planning of the 4-story building structure of the Central Java Prosecutor's Office includes the planning of the upper and lower structures. Planning the upper structure using SAP 2000 V14.2.2, while the lower structure is planned manually. The upper structure includes the planning of the roof, beams, columns, and floor plates of the building, while the lower structure includes the planning of the foundation. Loads that are reviewed for the design of structural elements are dead load, live load, and earthquake load. Earthquake load entered is dynamic earthquake load.